If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 3(x + -1) = 4x + -17 + 2x Reorder the terms: 2x + 3(-1 + x) = 4x + -17 + 2x 2x + (-1 * 3 + x * 3) = 4x + -17 + 2x 2x + (-3 + 3x) = 4x + -17 + 2x Reorder the terms: -3 + 2x + 3x = 4x + -17 + 2x Combine like terms: 2x + 3x = 5x -3 + 5x = 4x + -17 + 2x Reorder the terms: -3 + 5x = -17 + 4x + 2x Combine like terms: 4x + 2x = 6x -3 + 5x = -17 + 6x Solving -3 + 5x = -17 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. -3 + 5x + -6x = -17 + 6x + -6x Combine like terms: 5x + -6x = -1x -3 + -1x = -17 + 6x + -6x Combine like terms: 6x + -6x = 0 -3 + -1x = -17 + 0 -3 + -1x = -17 Add '3' to each side of the equation. -3 + 3 + -1x = -17 + 3 Combine like terms: -3 + 3 = 0 0 + -1x = -17 + 3 -1x = -17 + 3 Combine like terms: -17 + 3 = -14 -1x = -14 Divide each side by '-1'. x = 14 Simplifying x = 14
| 12t=9(t-15) | | 10.60+106= | | r^4=1024 | | 4u^2+4u-32= | | 9=r(r-8) | | 10.60-106= | | 7-(3n-3)=2-4n | | 2(x+2)+4x=x+5 | | 7r^2-10=25 | | 7x+8=x^2 | | 9(y+9)=8y-7 | | 6b^2-11b-35=0 | | -(b+1)=10-b | | 6a+3=-3(2a-1) | | 4x-10-6x+3=5-9x-7+2x | | 1500+8x=1500+12x | | 106-21.20= | | 6p=3(t+4)-t | | 8x^2-13=-8 | | 22-(x+5)=7x-7 | | 4x-14-6x+4=6-8x-8+2x | | 3y-5=5y+4 | | 6m^2+5m-4= | | 5d-d= | | 21.20-106= | | 4m^2+5=-57 | | 4x+39+12x-17=180 | | x+x+11=83 | | 7y-13-4y+8=0 | | A+1=37+a | | 7x^2+0.5x=0 | | 6x-5=18x+1 |